Beautiful Yetta : the Yiddish chicken - Pinkwater, Daniel Manus, 1941- (Feiwel and Friends, 2010)
Yetta, the beautiful chicken, breaks free from the truck that is carrying her to market. She quickly realizes the big city is nothing like the chicken farm. She is scared and confused until she meets and saves the life of a little, green parrot.